Doomed to grow? German municipalities in the stranglehold of a growth logic—a policy analysis of barriers to a circular urban transformation - Bahn-Walkowiak, Bettina; Wagner, Oliver; Krome, Carolina (Frontiers in Sustainability, 2025)
This paper explores the relationship between municipal finance, urban development, and environmental sustainability in Germany, with a specific focus on the potential for a circular economy to address persistent issues of land consumption. As centres of concentrated economic activity, urban areas are central to the achievement of sustainability goals, yet the German construction and housing sector operates largely within a linear system. Despite ambitious national targets, such as a goal to reduce land development to a net-zero increase by 2050, political objectives have not been met, and land consumption remains too high. The paper investigates whether institutional and structural barriers prevent municipalities from implementing effective sustainability measures. Using a two-part methodology, the research combines a narrative literature review on urban transformation, (post-)growth, and the circular economy with a quantitative data analysis. The data analysis utilises the INKAR database to examine land consumption, population density, tax revenues, and debt in German municipalities with the highest land consumption in 2022. The literature review suggests that the current political and financial systems in Germany create a systemic bias towards growth, as municipalities are incentivised to expand to generate income and compete for businesses and residents. While the data analysis finds that the correlation between financial pressure and land consumption is not statistically significant, indicating other factors may be at play, the findings of the literature analysis emphasise a conflict between municipal economic growth and environmental goals. The short-term financial gains of expansive development often come at the expense of long-term social and environmental costs. The paper reveals a research gap and addresses the lack of a clear explanation for why German municipalities, despite national policy, continue to consume land at an unsustainable rate, and provides new, counter-intuitive data on the role of municipal finance in this dynamic.